The effect of sectoral foreign direct investment on sectoral growth and sectoral employment in South Africa - Paul, Bernice Nicole (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
Over several decades past, developing countries have received increased amounts of Foreign Direct Investment (FDI). This form of investment has been welcomed because of the perceived benefits attached to it. FDI is seen as an important driver of economic development for many nations. For South Africa specifically, GDP growth rates have remained less than required, unemployment rates have reached staggering levels, poverty and inequality levels are increasing and the list goes on. Considering the perceived benefits of FDI, one may argue that FDI can play a crucial role in reducing the mentioned challenges facing the nation, however, only if directed to initiatives contributing to growth and employment. The 2015 Investment Policy Framework for Sustainable Development includes an action menu promoting investment in sectors relating to the achievement of the Sustainable Development Goals (SDGs). Therefore, this study is aimed at investigating the relationship between sector FDI and sector growth in addition to investigating the effect of sector FDI on sector employment over the period 2000Q1 to 2016Q4 for six of South Africa's economic sectors. The reason for such a study is based on the premise that developing nations such as South Africa lack sound trade and industrial policies favorable to foreign investors. This then leads to the nation failing to attract higher volumes of FDI which could be used to address structural challenges facing the country. It is therefore important to identify sectors in which FDI has resulted in growth and employment so that when policies are considered, the right FDI is targeted. A comprehensive review of existing theoretical and empirical literature showed that FDI does result in economic growth for developed and developing countries, although FDI crowds out domestic investment in the short run. Literature on the effect of FDI on employment showed diverse effects. Some studies found FDI to increase employment overall, other studies found FDI to increase employment only during periods of restructuring and some studies found FDI to result in job losses. For South African sectors, the present study finds that the financial services sector receives the highest volume of South African FDI, followed by the mining and quarrying sector and the manufacturing, however, FDI in all six sectors under study is associated with increased growth and employment. This finding suggests that the financial services sector has received increased volumes of FDI as a result of financialization of the South African economy. It is this increased FDI in the financial services sector that is directed to income redistribution from the real sector to the finance sector. This study employed econometric techniques and methods of analysis to investigate the relationship between sector FDI and sector growth, and the effect of sector FDI on sector employment. Panel cointegration tests were conducted for all six sectors included in the study to establish if long run equilibrium relationships exist among integrated variables. The Johansen-Fisher panel cointegration test revealed that there is evidence of cointegration in four of the six sectors. Since cointegration was established, the study proceeded to perform the Dumitrescu-Hurlin panel causality analysis and estimate a Panel Vector Error Correction Model (VECM). Results from the causality analysis found a unidirectional causality relationship between FDI and GDP growth, while the panel VECM found FDI to have a significant effect on growth in all sectors. The Seemingly Unrelated Regression (SUR) model employed to investigate the effect of FDI on employment found FDI to have an insignificant effect on employment in all sectors included, although the signs of the coefficients suggest that FDI is associated with increased employment and rising wages is associated with increased productivity growth. Since this study finds that FDI is associated with increased GDP growth in all six sectors under study, policy makers should devise strategies to attract FDI in sectors such as the transportation, storage and communication sector and the electricity, gas and water sector as FDI in these sectors are associated with increased growth however, they receive very low levels of FDI. There are a number of reasons for this, therefore, government institutions and policy makers should investigate the reasons for these low levels of FDI inflows into these sectors so that they can devise further strategies to address these reasons and perhaps attract higher levels of FDI into these sectors. Spillover benefits play a major role in host nations participating in FDI therefore, prior to entering into bilateral treaty agreements, policy makers should ensure that foreign investors are compelled to create jobs, offer training and qualifications etc. through their investments so that some of the SDGs can be achieved. Additionally, this study finds a positive, statistically insignificant relationship between FDI and employment. FDI may not have a significant relationship on employment due to jobless growth and capital-intensive growth rather than labor-intensive growth. Such a situation calls for government intervention. Skills shortage is a rising problem in South Africa; therefore, investors choose to employ advanced technologies rather than people. Under such circumstances, governments are encouraged to invest resources into skills development so that human capital are not completely replaced by technology.
Keywords: Investments, Foreign -- South Africa; South Africa -- Economic conditions -- 1991-; South Africa -- Economic policy; Gross domestic product -- South Africa; UNCTAD-ICTSD Project on IPRs and Sustainable Development; Unemployment -- South Africa